The challenges of Islamic Finance Institution in Malaysia : a case study at Bank Islam Malaysia Berhad (BIMB) UITM Puncak Alam / Intan Syuhada Shahirman - Shahirman, Intan Syuhada (Academy of Contemporary Islamic Studies (ACIS), 2016)
Islamic financial institution has growth rapidly in Malaysia since it has been introduced in 1970. It has been in existence for more than 30 years. The Enforcement of Islamic Banking Act 1983 allows the first Islamic bank established in the country and so on, with the liberalization of the Islamic financial system, more Islamic financial institutions have been established. Today, many Islamic finances in Malaysia were globally connected to others country such as Islamic foreign exchange. Malaysia continues to thrive and develop this industry by encouraging foreign financial institutions to establish an international Islamic banking business in Malaysia to undertake foreign currency business. Furthermore, Islamic finance plays an important role in this country that is accordance with shariah-compliant. This research discusses about the concept of management, the issues and challenges in Islamic finance. In addition, this research also plans to study the development and contribution of new products and innovation in Islamic finance. Therefore this study had conducted an interview sessions with Tuan Haji Azmi to find out if the problem still exists and what medium is suitable to use to disseminate the information. As a result, the findings from the data collected shows that Islamic finance institution in Malaysia faced many challenges from the aspect of management, customer and the facilities. As a result, the findings from the data collected shows that Islamic finance institution in Malaysia faced many challenges from the aspect of management, customer and the facilities.